2007
DOI: 10.1086/521553
|View full text |Cite
|
Sign up to set email alerts
|

ASpitzerStudy of the Mass-Loss Histories of Three Bipolar Preplanetary Nebulae

Abstract: We present the results of far-infrared imaging of extended regions around three bipolar preplanetary nebulae, AFGL 2688, OH 231.8+4.2, and IRAS 16342À3814, at 70 and 160 m with the MIPS instrument on the Spitzer Space Telescope. After a careful subtraction of the point-spread function of the central star from these images, we place constraints on the existence of extended shells and thus on the mass outflow rates as a function of radial distance from these stars. We find no apparent extended emission in AFGL 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Recent Spitzer/MIPS observations by Do et al (2007) have not revealed circumstellar dust shells around CRL 2688, as reported with ISO. The latter were reported by Speck et al (2000) who identified dust shells of about 2-3 pc in two post-AGB stars.…”
Section: Introductionsupporting
confidence: 64%
“…Recent Spitzer/MIPS observations by Do et al (2007) have not revealed circumstellar dust shells around CRL 2688, as reported with ISO. The latter were reported by Speck et al (2000) who identified dust shells of about 2-3 pc in two post-AGB stars.…”
Section: Introductionsupporting
confidence: 64%
“…For example, in the case of Y CVn, an extended dust -10shell is clearly seen in ISO maps (Izumiura et al 1996) with about the same size as inferred by Yetal95, but only very faintly in the Cetal12 study. However, for CRL2688, where Speck et al (2000) reported the presence of two dust shells from ISO scan data, Spitzer imaging by Do et al (2007) showed no such shells at a level well below the intensities expected from the ISO results. We believe that a detailed re-investigation is needed to resolve such discrepancies in results related to the presence of extended dust shells as derived from IRAS and ISO, and from the more recent Spitzer and Herschel missions (utilizing modern large-format detector arrays).…”
Section: Duration Of Mass Loss and Circumstellar Massmentioning
confidence: 66%
“…However, the formula of Baud & Habing (1983) applied to an OH 1612 MHz maser peak flux of 9 Jy (Likkel & Morris 1988) yields a much higher mass loss rate of Ṁ(OH) = 1.7 ∼ 4.9 × 10 −5 M ⊙ yr −1 (with V exp = 46 km s −1 from our 12 CO line). Do et al (2007) fitted the Spitzer MIPS 70µ images with a two shell model, and obtained Ṁ(70µ) = 0.4 ∼ 3 × 10 −5 M ⊙ yr −1 for an inner smooth CSE and Ṁ(shell) = 0.4 ∼ 3 × 10 −4 M ⊙ yr −1 for an outer extended dust shell (assuming a gas-to-dust mass ratio of 200 and V exp = 15 km s −1 . Here we note that our measured 12 CO expansion velocity of 46 km s −1 may not be that of the dusty CSE, see the discussion in § 4.2).…”
Section: The Low 12 Co Mass Loss Ratementioning
confidence: 99%